Analisis Pengaruh Kecerdasan Emosional dan Kecerdasan Spiritual Terhadap Kinerja Karyawan Perusahaan Daerah Air Minum Tirta Peusada - Syardiansah Syardiansah; Afriadi Afriadi; Muhammad Nur Daud (Universitas Negeri Medan, 2018)
This study aims to determine the effect of emotional Quotient and spiritual Quotient on employee performance at PDAM Tirta Peusada, East Aceh Regency. The number of samples in this study is 65 respondents using non-probability sampling technique that is saturated sampling. Data analysis method used is multiple linear regression analysis, t test, F test, and analysis of the coefficient of determination. The regression equation obtained is K = 2.138 + 0.442X1 + 0.218X2. The results of this study explain that emotional Quotient and spiritual Quotient have a significant effect on employee performance at PDAM Tirta Peusada, East Aceh District, where from the results of the t test, the value of t sig is obtained. emotional Quotient variable is 0.018 <0.05, and spiritual Quotient variable is 0.033 <0.05. Emotional Quotient and spiritual Quotient simultaneously have a significant effect on employee performance at PDAM Tirta Peusada, East Aceh Regency, where the F test results obtained t sig values. 0.011 <0.05. From the analysis of the coefficient of determination, it is known that emotional Quotient and spiritual Quotient affect employee performance at PDAM Tirta Peusada Aceh Timur by 47.2%, while the remaining 52.8% is influenced by other variables outside this research model.